Do Corporate Social Responsibility and Investor Protection Limit Earnings Management? Evidence from Indonesia and Malaysia - Muliati Muliati; Arung Gihna Mayapada; Abdul Pattawe (Journal of Accounting and Investment, 2021)
Research aims: This study aims to investigate the effect of corporate social responsibility on earnings management by considering the impact of investor protection.Design/Methodology/Approach: This study’s population was plantation companies listed in Indonesia Stock Exchange and Malaysia Stock Exchange. The period of this study was from 2012 to 2017. Moreover, the hypotheses testing technique used was multiple regression analysis.Research findings: This study’s results revealed that corporate social responsibility disclosure and investor protection significantly affected earnings management.Theoretical contribution/Originality: These results support the ethics hypothesis stating that companies committed to ethics view earnings management unethical behavior. This study also verifies the relationship between legal systems and earnings management.